O habitar vertical: um novo olhar para as coberturas urbanas - Silva, Alana Rodrigues da (Universidade do Vale do Rio dos Sinos, 2024)
Cities are becoming increasingly vertical and dense, resulting in a significant shortage of available space for creating new urban environments. In response to this spatial limitation, building roofs emerge as a viable alternative for creating new spaces for decompression and coexistence in urban areas. However, when creating these new rooftop spaces, it is critical to ensure an effective connection between these elevated spaces and pedestrians on the streets. Furthermore, this integration contributes to the promotion of compact neighborhoods, where walking is encouraged and facilitated. In this scenario, to enable the redefinition of roofs, the research develops specific guidelines that help in defining ideal buildings and uses for this transformation. These guidelines include considerations about accessibility, urban integration and the creation of visual and physical connections between rooftops and street level. To achieve this, these guidelines were applied in the city of Porto Alegre, in the Bom Fim neighborhood, selected as a case study. The choice of this neighborhood was strategic due to its population density and the need for additional living spaces. The findings achieved, together with all the knowledge acquired in the research, demonstrate that it is possible to create leisure and decompression spaces on the roofs, maintaining a harmonious connection with the street level. From the applications carried out and the results obtained, it was clear that this approach can be replicated in any location, not limited to the neighborhood studied.
Keywords: Cidades; Densidade urbana; Cidades compactas; Edificações em altura; Coberturas; Cities; Urban density; Compact cities; Buildings; Roofs; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo